Faktor Yang Berhubungan Dengan Kejadian Keputihan (Flour Albus) Pada Wanita Usia Subur di TPMB Salifiyah Tahun 2024 - Nur Fathur Rohmah, Hajar; Nafisah, Fitri; Sarani Siagian, Fati (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Kesehatan Salsabila Serang, 2025)
Leucorrhea or Flour Albus is a condition where the vagina discharges a fluid or mucus resembling pus (Bahari, 2020). Leucorrhea is a reproductive health issue in women characterized by a white or mucous discharge from the vagina, which may or may not have an odor (Hastuty et al., 2023). According to statistical data, the population in West Java Province reaches 11,358,740 people, with 27.60% experiencing leucorrhea. The majority of women affected by leucorrhea are those of reproductive age, specifically between 10–24 years (Suyenah & Dewi, 2022). This study aims to identify the factors associated with the occurrence of leucorrhea (Flour Albus) among women of reproductive age at TPMB Salifiyah in 2024. This research employed a cross-sectional study design. The population consisted of all women of reproductive age, totaling 60 respondents, all of whom were included as the sample. Data analysis was performed using univariate and bivariate analysis with the chi-square test. The data analysis revealed that the variables associated with the occurrence of leucorrhea among women of reproductive age included vulvar hygiene practices (p=0.000), pantyliner usage (p=0.001), obesity (p=0.000), physical activity (p=0.000), knowledge (p=0.000), and the use of vaginal cleansing solutions (p=0.006). All the variables studied showed a significant relationship with the occurrence of leucorrhea among women of reproductive age. Women of reproductive age are advised to avoid excessive use of vaginal cleansing solutions, maintain a normal body weight, refrain from using pantyliners, practice proper vulvar hygiene, avoid excessive physical activity, and enhance their knowledge to prevent leucorrhea.